Empowering Digital Business Bagi Pegiat Usaha Online Kota Malang - Rifki Hanif; Agus Purnomo Sidi; Ahmad Nizar Yogatama; Muhammad Bukhori; Widiya Dewi Anjaningrum (Jurnal Pengabdian Masyarakat, 2020)
To start a business in the digital age, every business person must be able to understand how to market in the digital era as it is today. An effective way that can be done is through inbound marketing. This community service activity is intended to train online businesses activists in Malang, especially entrepreneurs who have a business start-up in order to manage online marketing effectively and consistently. Digital Business Empowering Training Activities for Online Business Activists in Malang is done in the form of a tutorial delivered directly by the speaker. where based on the results of this dedication, online business activists in Malang are very interested and eager to participate in similar activities for the development of business knowledge.